Mexican visual cornucopia: The photographs of the book México sus recursos naturales, su situación actual, 1922 - Barbosa, Carlos Alberto Sampaio [UNESP] (EDIPUCRS, 2018)
The objective of this article is to understand how Mexico made use of a visual discourse, more precisely photographic, as a strategy of diplomatic, cultural and political propaganda in Brazil. For that I will use as a source and object the book “México sus recursos naturales, su situación actual: homenaje al Brasil en ocasión del primer centenario de su independencia 1822-1922. This book, edited by the Secretaría de Industria Comercio y Trabajo, has 320 pages. The construction of his narrative is largely anchored in photographs, which demonstrates the importance that the image had for the Mexican authorities. This publication is part of the Mexican participation in the exhibition commemorating the Centennial of Independence of Brazil, held in Rio de Janeiro in 1922. The book is part of a wide Mexican participation in this exhibition that had a pavilion, murals, films and other visual devices.
Cornucopia visual mexicana: Las fotografías del libro México sus recursos naturales, su situación actual, 1922
Cornucópia visual mexicana: As fotografias do livro México seus recursos naturais, sua situação atual, 1922
Keywords: Centennial of independence; Mexico revolutionary; Photography